The relationship between core endurance, physical activity level and balance in office workers - Yentur, Songul Baglan; Yarasir, Ezgi (Taylor & Francis Ltd, 2024)
Objectives. The aim of this study was to evaluate the relationship between core endurance tests and physical activity level, balance, ergonomics and pain in office workers. Methods. The study included 57 office workers who had been employed for at least 1 year. Core endurance was assessed using McGill core endurance tests. Physical activity, balance, pain and ergonomic risks were evaluated with the international physical activity questionnaire (IPAQ), timed up and go (TUG), visual analog scale (VAS) and rapid office strain assessment (ROSA), respectively. Results. A significant correlation was found between balance and static core endurance tests. However, no significant correlation was found between ergonomics and physical activity level and core endurance tests except for trunk extension and prone bridge tests. In addition, there was a significant difference in core endurance tests for patients with and without regular exercise habits. Waist circumference and hip circumference measurements were found to be significantly negatively associated with static core tests. Conclusion. Core endurance was found to be associated with exercise habits, balance, hip and waist circumference and ergonomics in office workers. Improving core endurance may be beneficial for preventing musculoskeletal risks in office workers.
Keywords: office workers; core endurance; physical activity level; balance